Network Pharmacology and Molecular Docking Study on the Mechanism of the Therapeutic Effect of Strychni Semen in NSCLC - He Geng; Yujie Xue; Binghua Yan; Zhaoxue Lu; Hengjin Yang; Peng Li; Jundong Zhou (Biological Procedures Online)
Abstract Strychni Semen, characterized by its bitter taste and warm properties, has been confirmed to possess anti-tumor properties. However, the molecular mechanism of Strychni Semen in treating non-small cell lung cancer (NSCLC) needs further study. This study aimed to explore the molecular mechanism of Strychni Semen in treating NSCLC based on network pharmacology and molecular docking. The active components and targets of Strychni Semen were retrieved from the TCMSP, supplemented by the HERB database and the related literature. NSCLC-related targets were retrieved from the GeneCards, OMIM and DisGenet databases. The intersection targets of Strychni Semen in treating NSCLC were obtained via an online platform. The Protein-Protein Interaction (PPI) network was subsequently constructed to deeply analyse the interrelationship of the intersection targets via the String database. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were carried out via the Metascape database. The interactive networks between Strychni Semen and NSCLC were constructed via Cytoscape 3.9.1. Molecular docking detected interactions between the key components and the core targets. The core targets were validated via GEO datasets. 21 active components and 67 targets were identified, with 47 associated with NSCLC. The key active components were Stigmasterol, IcarideA, 2-Hydroxymethylanthraquinone, (+)-catechin, (2R)-5,7-dihydroxy-2-(4-hydroxyphenyl)chroman-4-one, (S)-Stylopine, Brucine and Isobrucine. The core targets were PTGS2, NR3C1, ESR1, CASP3 and PRKACA. Molecular docking revealed that these compounds undergo strong binding affinity with the core genes. GEO database indicated that PTGS2 was the most promising core target. In addition, Strychni Semen’s effects on NSCLC involved mainly the Calcium pathway, the Estrogen pathway, and the cGMP-PKG and cAMP pathways. This study visually demonstrated the mechanism of the therapeutic effect of Strychni Semen in NSCLC through multiple components, targets and pathways which provides a basis for clinical treatment and further experimental research.